The assessment of patient-centred care among diabetic patients in southern Malawi - Makwero, Martha (University of the Witwatersrand, Johannesburg, 2024)
Introduction: Patient centred care (PCC) is gaining recognition in various quality care reforms, especially in the growing era of chronic care where its effects are palpable yet its functional elements are unknown and hardly measurable. PCC has been shown to improve care processes and patient reported outcomes among chronic care patients such as Diabetes Mellitus (DM). While the Malawi Quality management Directorate (QMD) and the Non-communicable disease and injury (NCDI) policies mention PCC as a strategic quality reform, its functional elements are hardly known and, if it matters, in mediating patient experiences and outcomes. It is clear that the vagueness is thwarting PCC’s implementation, assessment, and advocacy. Thus, as the burden of chronic diseases, including DM grows, there is a need to optimize PCC through the elicitation of its functional elements, its objective assessment, and its recommended implementation strategies. Aim: This study aims to assess the functional elements of PCC and its relationship to outcomes in diabetic patients. Methodology: I conducted a cross-sectional, exploratory mixed methods study in southern Malawi. Sequentially, I employed qualitative and quantitative methods in order to enrich the contextual understanding of the complex PCC construct and its correlates. Therefore, we initially explored the common elements of PCC in LMIC through a scoping review. Building on the findings, in the next phase, I explored PCC conceptualization among three stakeholders (patients, health care providers and policy makers) further, breaking down the PCC construct to its functional elements through a qualitative inquiry. The qualitative themes identified were used to build a tool on important elements of PCC from the same population. A psychometric analysis was done in order to confirm the structure and consistency of the tool to improve the validity of results obtained. Thereafter, I quantitatively measured the current PCC practice ix among patients with DM and its association with baseline adherence to DM care plans, self- efficacy, glycaemic control, and some complications. The study used Covidence to manage the scoping review and Nvivo version 11 for the qualitative data, which was analyzed through the thematic analysis. The quantitative data was analyzed using STATA version 18 and R-studio version 4.2.3. The psychometric analysis employed exploratory and confirmatory factor analysis. Dichotomization of study participants into those who perceived low and high PCC scores was done through K-means clustering was done in R studio. Similarly, correlational studies and Path analysis were conducted to determine the nature and direction of relationships between the perception of PCC during the encounter and adherence, self-efficacy and glycaemic control. Results: The study confirmed the paucity and fragmentation of literature on PCC in LMIC especially in Africa and therefore, the need to situate the elements in our context. The themes identified were interrelated, and differences in expression and emphasis of some of the elements compared to the Eurocentric ones were highlighted. The recurring themes included the facilitating ambience, sharing of information, and patient involvement, the wider organization of care and the macroenvironment in which care takes place. Although they are similar to the Eurocentric themes, our qualitative inquiry identified eight themes and proposed a working definition. Thus, in the Malawian context, PCC was conceptualized as an expected care process that incorporates warm patient reception, where the healthcare provider consciously aims to reduce the patient-HCP power gap to harness a good long-term relationship. This creates a conducive atmosphere that allows the gathering of information that holistically identifies the individual specific problems and all possible interacting factors, ensuring timely access to care and medication. While patients highlighted the value of PCC encounters, particularly shared decision-making, the study documented the x challenges and vulnerabilities faced in an attempt to engage their providers in shared decision making. The psychometric analysis identified three latent themes underlying the PCC elements namely 1) relational aspects of care, 2) individualization and shared decision making and, 3) organizational aspects of care highlighting what is important and the hierarchical nature of the PCC construct. While acknowledging the need for further refinement, the tool exhibited acceptable reliability and validity properties to be used as a measurement framework in the study. The study showed significant deficiencies in the delivery of PCC with 55.8% of patients perceiving low levels, particularly, in the area of individualization and shared decision-making. Higher PCC scores did not have a significant relationship with self-efficacy. Both the perception of PCC and self-efficacy were positive predictors of adherence independently. Having perceived higher PCC scores was associated with a marginal 0.03-point increase in one’s adherence scores (β = 0.03; 95% CI: 0.01 to 0.04, p-value <0.001). Self-efficacy and adherence were both positive predictors of blood sugar control independently. Better self- efficacy was associated with a 0.03 unit decrease in the level of HbA1c (β =-0.03; 95% CI: - 0.04 to -0.022, p-value <0.001). Additionally, as adherence scores went higher, there was a 0.15 unit decrease in HbA1c (β = -0.15; 95% CI: -0.25 to -0.02, p-value <0.05). The results highlight that PCC can affect glycaemic control only indirectly through adherence. Conclusion The study has confirmed the complexity of the PCC construct and the paucity of literature in LMIC. It has highlighted that above and beyond creating a conducive ambiance, medical encounters ought to evoke support and capacitation for patients to undertake self-care behaviors confidently to be able to produce patient outcomes. Even though this study is cross- xi sectional, the initial patterns are promising for the value of PCC in mediating patient-reported experiences and outcomes among DM patients.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; patient-centred care; shared decision making; adherence; self-efficacy; SDG-3: Good health and well-being